PENGARUH PROPORSI AIR DAN ETANOL SEBAGAI PELARUT TERHADAP AKTIVITAS ANTIOKSIDAN ANGKAK BIJI DURIAN DENGAN METODE PHOSPHOMOLYBDENUM DAN DPPH - Subianto, Christine; Srianta, Ignatius; Kusumawati, Netty (Widya Mandala Surabaya Catholic University, 2013)
Angkak is rice fermented product by Monascus sp. Beside rice, durian seeds can be a substrate of Monascus sp. Monascus sp. produces some antioxidant metabolites during fermentation. The purpose of this research investigated the effect of proportion of water and ethanol as solvent for antioxidant activity of durian seeds angkak with phosphomolybdenum and DPPH method. The proportions of water and ethanol as solvents were 100:0 (E0) ; 80:20 (E20) ; 60:40 (E40) ; 40:60 (E60) ; 30:70 (E70) ; and 20:80 (E80) (v/v). ANOVA’s result (α=5%) showed that proportion of water and ethanol as solvent interacted pigment content and antioxidant activity of durian seeds angkak. Yellow pigment was dominant pigmen in durian seeds angkak. Ethanol 40% was most effective solvent and ethanol 80% was not effective solvent to extraction durian seeds angkak pigment. The higher antioxidant activity of durian seeds angkak was ethanol 40% (0,5876 mg AAE/g sample (wb)) for DPPH method and ethanol 0% (6,7899 mg AAE/g sample (wb) and 6,4247 mg GAE/g sample (wb)) for phosphomolybdenum method.